Advances in Cryptology -- CRYPTO 2019 : 39th Annual International Cryptology Conference, Santa Barbara, CA, USA, August 18-22, 2019, Proceedings.: 39th Annual International Cryptology Conference, Santa Barbara, CA, USA, August 18-22, 2019, Proceedings. Part I (2019) - Unknown
No abstract available